Use of medicinal plants as feed additives in the diets of Mozambique tilapia (Oreochromis mossambicus) and the African Sharptooth catfish (Clarias gariepinus) in Southern Africa - Mbokane, Esau Matthews; Moyo, Ngonidzashe Adreck Gukuta (Frontiers in Veterinary Science, 2022)
Mozambique tilapia (Oreochromis mossambicus) and the African Sharptooth catfish (Clarias gariepinus) are the most farmed freshwater fish species in Southern Africa. However, production in the freshwater aquaculture sector has remained low due to, among other key factors, high cost of feeds, disease outbreaks, and poor sexual development in broodstock. Small-scale farmers are affected the most because they often lack resources and cannot afford expensive commercial diets, antimicrobials, and synthetic hormones needed to regulate reproduction. Among the proposed solutions, the inclusion of medicinal plants as feed additives is the most promising alternative to enhance growth performance, disease resistance and reproduction in fish. Plants contain various compounds such as polyphenols, carbohydrates, amino acids, flavonoids, alkaloids, tannins, organic acids, volatile oils, polysaccharides, minerals, and vitamins, some of which are necessary for growth and improving immunity or overall wellbeing in fish and other animals. However, the utilization of plants as feed additives in aquafeeds is still limited in Southern Africa. This paper reviews the potential role that medicinal plants can play as feed additives in order to promote growth performance, immunity, disease resistance, and reproduction in the culture of O. mossambicus and C. gariepinus in Southern Africa. The objective was to consolidate information about plants that can be specifically applied in freshwater aquaculture in Southern Africa by highlighting their availability and efficacy as either growth promoters or immunostimulants or fertility enhancer.